Masterchefs. Issue 5 (2nd May 2021) - Samuels, Michelle
Abstract : London Early Years Foundation scooped the gong for Health and Well-Being at the Nursery World Awards 2020. Michelle Samuels, LEYF apprentice manager, talks about the LEYF Early Years Chef Academy and associated qualification which clinched it the top spot